Semantic keyword-based search on structured data sources : Third International KEYSTONE Conference, IKC 2017, Gdańsk, Poland, September 11-12, 2017, Revised Selected Papers and COST Action IC1302 Reports /: Third International KEYSTONE Conference, IKC 2017, Gdańsk, Poland, September 11-12, 2017, Revised Selected Papers and COST Action IC1302 Reports. (2018) - Unknown
No abstract available